Hot deformation behavior and processing map of Mg-12Gd-1MM-0.6Zr magnesium alloy. Issue 1 (February 2020) - Li, B B; Shi, G L; Zhang, K; Wang, K K; Li, X G; Li, Y J; Ma, M L; Yuan, J W
Abstract: The hot deformation behavior of Mg-12Gd-1MM-0.6Zr (wt.%) magnesium alloy was tested by Gleeble-1500D hot simulator with reduction of 60% and strain rates from 0.001 to 1 s −1 at the temperature range from 753 to 793 K. The results show that the flow stress is influenced by both, temperatures and strain rates. At constant temperatures, flow stress is increased with strain rate, while at constant strain rates, it decreased with temperature. The constitutive equation of Mg-12Gd-1MM-0.6Zr alloy during hot compression was constructed by the linear regression analysis. Average activation energy and stress exponent were 227.94 kJ/mol and 2.87, respectively. The processing map was plotted and analyzed via the dynamic material model. The most proper ranges for hot deformation temperature and strain rate were found to be 763 to 783 K and 0.01 to 0.1 s −1, respectively.